Structural Model of Competitive Advantage as A Basis for Empowering Batik MSMEs - Rohadin Rohadin; Agus Purwanto; Heriyono Heriyono; Susi Sugiyarsih; Fahmi Maulana (PT. Riset Press International, 2026)
This study aims to analyze the determinants of the competitive advantage of batik MSMEs in Cirebon Regency amid pressure from imported products and intense competition. Using Structural Equation Modeling (SEM), this study examines the relationships among market orientation, dynamic capabilities, and innovation. The results of the outer and inner model evaluations indicate that the competitive advantage of batik SMEs is achieved through the strengthening of innovation and the dynamic capabilities of owners or managers. These findings confirm that effective operational innovation requires integration between a sharp market orientation and strong dynamic capabilities. The implications of this study suggest that, to create sustainable competitiveness, SME empowerment strategies must focus on enhancing managerial capacity to respond to market changes and on fostering product creativity. In a contributive way, this study enriches strategic management theory by highlighting the importance of synergy between internal (capabilities) and external (market) factors in generating competitive advantage within the local creative industries sector.